Targeting Social Transfer Programmes: Comparing Design and Implementation Errors Across Alternative Mechanisms. (November 2015) - Sabates‐Wheeler, Rachel; Hurrell, Alex; Devereux, Stephen
Abstract: An innovative cash transfer programme in northern Kenya is the first of its kind to trial three targeting mechanisms to learn about which approach is most effective at identifying the poorest households while minimising inclusion and exclusion errors. Analysing data collected through a randomised controlled trial, we conclude that community‐based targeting is the most accurate of the three approaches, followed by categorical targeting by age and household dependency ratio. However, targeting performance is strongly affected by implementation capacity and modalities. Through a simulation exercise, we show that a proxy means test would have performed better than single categorical indicators. © 2015 UNU‐WIDER. Journal of International Development published by John Wiley & Sons, Ltd.